Pemanfaatan Sumber Informasi oleh Pemustaka di Dinas Perpustakaan dan Kearsipan Kota Padang - Fauziah, Husnil; Nurizzati, Nurizzati (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2019)
Abstract The writing of this paper seeks to describe the use of information resources by users at the Padang City Library and Archives Service. Data collected using descriptive research methods with research objects of various sources of information in the library. Data was collected through questionnaires and interviews with librarians and librarians in the Padang City Library and Archives Office library through literature studies in accordance with the problem under study. Based on the discussion of the data it can be concluded that the utilization of information sources by the library users in the Padan City Library and Archives Service is as follows: (1) Information sources that can be used by visitors in the Library of the Padang City Library and Archives Service, such as public collections numbered from 000 public works to 900 history and geography. Then there is also a source of information that is a collection of references consisting of dictionaries, encyclopedias, laws, altas, handbooks. And there is also a collection of reservoirs which are numbered from a collection of 000 public works to a collection of 900 history and geography. (2) the utilization of information resources in the library can be seen from the user's needs, user motives, user interests. (3) the opinion of the user towards the information sources in the library can be seen from the completeness of information sources in the library such as: information sources as opportunities for career achievement and achievement, updating information sources, completeness of information sources, as a means of decision making, information sources as entertainment. The information retrieval facility can be seen from the use of collections, the condition of book fiqs, the arrangement of books in the library, the search tools facility, the enhanced facilities.Keywords: utilization, information, users